Development of Interactive Learning Media Integrated with the Problem-Based Learning Model on Work and Energy Material - Sulfa, Sulfa; Kafrita2, Nova; Wiratama, Arif (Science and Mathematics Education Journal, 2025)
This research aims to determine the development, validity, and practicality of interactive learning media integrated with the Problem-Based Learning model on work and energy material. The type of research in this study is Research and Development (R&D) using the ADDIE development model. The sample in this research consists of 5 students from class VIII A of SMP N 1 Muaro Jambi for the small group trial, and 29 students from class VIII B of SMP N 1 Muaro Jambi for the large group trial. The data analysis technique in this study is the Likert scale, used to measure the validity and practicality of the developed learning media. The results of this study show that the validity falls under the "Very Valid" category with an average percentage of 83,79% from media and material expert validation. The small group trial resulted in a percentage of 75,2% with the "Practical" category, requiring some improvements, while the large group trial showed a percentage of 86,6% with the "Strongly Practical " category. The teacher response survey yielded a percentage of 90.7%, categorized as "Strongly Practical." Thus, the interactive learning media integrated with the Problem-Based Learning model on work and energy material is feasible for use in research and can be effectively implemented by both students and teachers.